Shirin Amaare: Bellisma-Urge Gele Headdress - Sussie Aku Damalie (Fashion and Textiles Review)
The paper is of qualitative paradigm centred on practice-based research design. It highlights the creative process of a headdress style exhibit fashioned for a Millennial Muslim bride’s walima (celebration/reception) using indigenous African resources. The main materials used are “Epele” fabric from Northern Ghana and classic Gele fabrics used in Southern Nigeria. Non-routine design is adopted to impact the outcome. The results are thematically analysed to reflect the use of culture trends, fashion innovation, creativity and production in meeting the needs of the contemporary Ghanaian Millennial Muslim bride. The beautiful headdress accessories wrapped in local African fabrics (from Northern Ghana and Nigeria) are gorgeous with a focus on style, materials and method. The attractive Bellisma-Urge head wraps created give the Millennial Muslim Bride that dazzling look perfect for holding the attention of the groom and every guest; making her the real ‘centre’ of attraction deservedly.